2016
DOI: 10.3847/0004-637x/822/2/86
|View full text |Cite
|
Sign up to set email alerts
|

False Positive Probabilities for All Kepler Objects of Interest: 1284 Newly Validated Planets and 428 Likely False Positives

Abstract: We present astrophysical false positive probability calculations for every Kepler Object of Interest (KOI)-the first large-scale demonstration of a fully automated transiting planet validation procedure. Out of 7056 KOIs, we determine that 1935 have probabilities <1% to be astrophysical false positives, and thus may be considered validated planets. 1284 of these have not yet been validated or confirmed by other methods. In addition, we identify 428 KOIs likely to be false positives that have not yet been ident… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
510
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 461 publications
(523 citation statements)
references
References 52 publications
9
510
4
Order By: Relevance
“…Of these planets, about 75% have been discovered by the transit method, which has greatly benefited from the data obtained with the Kepler Space Telescope (Borucki et al 2010). Moreover, in 2014 alone, 715 new planets in 305 systems were detected by Kepler, almost doubling the number of exoplanets known at that time (Lissauer et al 2014;Rowe et al 2014), and more recently, Morton et al (2016) have confirmed nearly 1280 new transiting Kepler planets based on probabilistic validation methods. Most of the remaining 25% of planets have been found using the radial velocity (RV) technique.…”
Section: Introductionmentioning
confidence: 81%
“…Of these planets, about 75% have been discovered by the transit method, which has greatly benefited from the data obtained with the Kepler Space Telescope (Borucki et al 2010). Moreover, in 2014 alone, 715 new planets in 305 systems were detected by Kepler, almost doubling the number of exoplanets known at that time (Lissauer et al 2014;Rowe et al 2014), and more recently, Morton et al (2016) have confirmed nearly 1280 new transiting Kepler planets based on probabilistic validation methods. Most of the remaining 25% of planets have been found using the radial velocity (RV) technique.…”
Section: Introductionmentioning
confidence: 81%
“…This became possible only recently thanks to the Kepler Space Telescope (Borucki et al 2010). Thousands of small planet candidates have been detected by Kepler (Borucki et al 2011a,b;Batalha et al 2013;Burke et al 2014;Rowe et al 2015;Mullally et al 2015;Coughlin et al 2015), and the majority of them are either confirmed or believed to be bona fide planets (e.g., Fressin et al 2013;Lissauer et al 2012;Morton et al 2016). Several studies have been conducted to investigate the small planet-metallicity correlation based on the Kepler planet catalog.…”
Section: Introductionmentioning
confidence: 99%
“…That upper limit is typically at the 1% or 0.1% level in order to declare a candidate as a validated planet (e.g., Montet et al 2015;Crossfield et al 2016;Morton et al 2016). Hence, the validated planets have measured orbital periods and radii, but their masses are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Those candidates need to be examined by gathering additional data, to check whether the transit light curve is produced by a transiting star-planet system, or by a different scenario, making the object a false positive (e.g., Torres et al 2011;Fressin et al 2013). As there are insufficient observational resources needed for gathering the amount of data required to investigate the true nature of each transiting planet candidate, and because some planets cannot be confirmed with current observational capabilities, a statistical validation approach was developed (e.g., Torres et al 2011Torres et al , 2015Morton et al 2016). This approach uses a relatively small amount of observational follow-up data, typically including a single spectrum and a single high angular resolution image of the target, and is based on estimating the probability that the transit light curve is produced by a transiting star-planet system and not a false-positive scenario (e.g., Torres et al 2011;Morton 2012).…”
Section: Introductionmentioning
confidence: 99%